An Electricity Market Model with Generation Capacity Investment under Uncertainty - Andreas Schröder (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
This article presents an electricity dispatch model with endogenous electricity generation capacity expansion for Germany over the horizon 2035. The target is to quantify how fuel price uncertainty impacts investment incentives of thermal power plants. Results point to ndings which are in line with general theory: Accounting for stochasticity increases investment levels overall and the investment portfolio tends to be more diverse.
Keywords: C63; L13; L94; 330